Genesis and Composition of Calcium Carbonate Nodules (kankar) in The Different Landforms of The Ghaggar River Basin (Haryana and Punjab) - Ahuja, R L; Khanna, S S (Annals of Arid Zone, 2016)
Calcium carbonate nodules occurring in different landforms of the Ghaggar river basin were studied to determine their genesis, composition and distribution. Detailed investigations revealed that the depth of their occurrence was variable and not related with the water table. They were present not in the form of a hard layer but in scattered irregular patches within the pedons and at lower depths. The kankars containing soluble salts (EC 0.11 to 0.21 mmhos/cm), are alkaline in reaction (pH 7.6 to 8.3). Being calcareous and dolomitic in nature (CaO 12.04 to 34.72 per cent and MgO 3.0 to 13 0 per cent), their solubility parameter (12.1 to 13.3) is found to have a positive correlation with pH. The amount of calcium in kankars is also related with the calcium in surrounding ma&s. From their occurrence in recent landforms (levees, bars, and flood plains) which are lacking in pedogenic activity, development and aridity, it is inferred that the formation is of primary origin.